ТАЛАБАЛАРНИНГ АҚЛИЙ МЕҲНАТИ ВА УНИ ТАШКИЛ ЭТИШ ОМИЛЛАРИ - norboyeva, D (FILOLOGIYA UFQLARI JURNALI, 2021)
This article discusses the problem of innovative education in higher educational institutions, as well as staffing in the Republic of Uzbekistan. The proposed method of teaching in cooperation contributes to the achievement of a democratic style of community, encourages the imagination of students, stimulates the origin of original ideas, and develops the creative powers and abilities of students.